Asymmetric Yardstick Competition: Traditional Procurement versus Public-Private Partnerships - Giuseppe Di Liddo; Annalisa Vinella (Center for Economic Studies and ifo Institute (CESifo), 2019)
We investigate yardstick competition between local jurisdictions in which pure rent-seeking incumbents undertake an identical infrastructure project choosing be- tween two contractual arrangements with different financing profiles, namely traditional procurement (TP) and public-private partnership (PPP). We show that a mixed regime, in which TP is used in one jurisdiction and PPP in the other, is likely to arise when projects are mildly lucrative, and/or jurisdictions have a moderate fiscal capacity. We find that, in the mixed equilibrium, incumbents provide different levels of public services, face different probabilities of re-election, and obtain different rents. The adoption of different forms of project governance permits incumbents to disguise themselves and undermine voters' ability to assess their performances. Therefore, yardstick competition is hindered, even if jurisdictions display identical revenue capacities.
Keywords: D72; H77; 330; political yardstick competition; rent seeking; infrastructure projects; traditional procurement; public-private partnership